The Principle of Separation of Powers in Political Science - Bagratyan, Bagrat (WISDOM, 2016)
The twentieth century doctrine considers separation of powers as a mechanism of constitutional technique that must be present in Political Science. In order to achieve this particular sense of separation of powers, this doctrine is based on the principles of specialization and independence. Separation of powers, therefore, refers to the division of government responsibilities into distinct branches to limit any one branch from exercising the core functions of another. The intent is to prevent the concentration of power and provide for checks and balances and establishment of democratic society.